2015
DOI: 10.1016/j.jpeds.2015.08.053
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 Mediates Cardiorespiratory Disturbances during Infection in Neonates

Abstract: PGE2 and PGEM are rapidly elevated in CSF during an infectious event and may explain cardiorespiratory disturbances, which are the major presenting symptoms of neonatal infections. PGE2 and PGEM are released during bacterial infections and could serve as biomarkers for sepsis and autonomic dysfunction in neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 37 publications
6
42
0
1
Order By: Relevance
“…This would in part explain the interaction between chemosensitivity and the inflammatory system observed in several studies (Hofstetter et al, 2007;Siljehav et al, 2012;Siljehav et al, 2014;Forsberg et al, 2016). Moreover, in human neonates, rapid elevation of brainstem PGE2 during infectious events is associated with, and may explain, the initial presenting symptoms of infection, which are apnea, bradycardia, and desaturation (Siljehav et al, 2015). Because a hypercapnic challenge triggers a gap junction mediated release of PGE2 (Forsberg et al, 2016), we hypothesized that astrocyte stimulation would trigger a similar release.…”
Section: Resultsmentioning
confidence: 86%
“…This would in part explain the interaction between chemosensitivity and the inflammatory system observed in several studies (Hofstetter et al, 2007;Siljehav et al, 2012;Siljehav et al, 2014;Forsberg et al, 2016). Moreover, in human neonates, rapid elevation of brainstem PGE2 during infectious events is associated with, and may explain, the initial presenting symptoms of infection, which are apnea, bradycardia, and desaturation (Siljehav et al, 2015). Because a hypercapnic challenge triggers a gap junction mediated release of PGE2 (Forsberg et al, 2016), we hypothesized that astrocyte stimulation would trigger a similar release.…”
Section: Resultsmentioning
confidence: 86%
“…Furthermore, IL-1 and TNF receptors are found on microglia, neurons, astrocytes, and neurovascular endothelial cells (Lampron et al, 2013; Probert, 2015), suggesting inflammation can be sensed and further propagated by multiple cell-types in the CNS. For example, peripherally applied IL-1β induces prostaglandin synthesis in vascular endothelial cells of the blood brain barrier (BBB), which impairs respiration and is important for neonatal respiratory control during systemic infection (Hofstetter and Herlenius, 2005; Siljehav et al, 2015). Overall, the results of systemic inflammation are widespread in the CNS and multiple cell-types play important roles in mediating CNS inflammatory effects.…”
Section: Models Of Inflammationmentioning
confidence: 99%
“…Additionally, recent studies have shown that septic neonates with cardiorespiratory disturbances have increased PGE 2 levels. [13] In the current study, we used LPS as a TLR4 agonist to stimulate the neonatal innate immune response. Thus, our findings do not directly translate to observations made in humans infected with pathogenic organisms.…”
Section: Discussionmentioning
confidence: 99%
“…This may be of particular relevance during the neonatal period, where COX-2 expression and increased levels of circulating prostaglandins have been associated with multiple morbidities. [1113,2831]. We speculate that identifying the source of circulating prostaglandins may reveal unique pharmacologic targets to limit prostaglandin synthesis and associated neonatal morbidities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation